Perceived barriers and motivating factors influencing student midwives’ acceptance of rural postings in Ghana - Lori, Jody R (BioMed Central, 2012)
BACKGROUND: Research on the mal-distribution of health care workers has focused mainly on physicians and nurses. To meet the Millennium Development Goal Five and the reproductive needs of all women, it is predicted that an additional 334,000 midwives are needed. Despite the on-going efforts to increase this cadre of health workers there are still glaring gaps and inequities in distribution. The objectives of this study are to determine the perceived barriers and motivators influencing final year midwifery students’ acceptance of rural postings in Ghana, West Africa. METHODS: An exploratory qualitative study using focus group interviews as the data collection strategy was conducted in two of the largest midwifery training schools in Ghana. All final year midwifery students from the two training schools were invited to participate in the focus groups. A purposive sample of 49 final year midwifery students participated in 6 focus groups. All students were women. Average age was 23.2 years. Glaser’s constant comparative method of analysis was used to identify patterns or themes from the data. RESULTS: Three themes were identified through a broad inductive process: 1) social amenities; 2) professional life; and 3) further education/career advancement. Together they create the overarching theme, quality of life, we use to describe the influences on midwifery students’ decision to accept a rural posting following graduation. CONCLUSIONS: In countries where there are too few health workers, deployment of midwives to rural postings is a continuing challenge. Until more midwives are attracted to work in rural, remote areas health inequities will exist and the targeted reduction for maternal mortality will remain elusive.